Effect of Break- Even Analysis on Decision Making of Selected Listed Manufacturing Firms in Nigeria - Akinleye, Gideon Tayo; Olaniyi, Adebusoye (Journal of Danubian Studies and Research, 2023)
For the years 2012 through 2021, the researchers examined how the break-even method influenced the choices made by publicly traded Nigerian manufacturers. In particular, the study investigated into how many variables, including selling price, production cost, and sale volume, affected the net profit of publicly traded manufacturing enterprises in Nigeria. The study used a retrospective study to collect data from secondary sources. Twenty-five (25) enterprises selling consumable items that were traded on the floor of the Nigeria Exchange Group on May 30, 2022 make up the study population. Only 15 of the 25 companies producing consumer items were chosen at random for the study. The information was culled from the audited financial statements of fifteen (15) randomly selected manufacturing enterprises over a ten (10) year time span (2012-2021). Descriptive and other estimating methods were used to examine the compiled data. The study's choice-making (dependent variable) was evaluated by net income. The research showed that the cost of production has a negative influence on listed manufacturing businesses' profit after tax, whereas selling price and sale volume both have positive and substantial effects on profit. According to the results, break-even analysis may have a positive or negative study on the decision-making of Nigerian manufacturing enterprises, depending on how the profit is calculated. Management of Nigerian factories was thus urged to use any and all means at their disposal to bring down the cost of production in manufacturing of maximizing profits.